Performance of thermally modified timber (TMT) in outdoor application – durability, abrasion and optical appearance - Christian R. Welzbacher (University of Zagreb, Faculty of Forestry and Wood Technology, 2009)
Thermally modified timber (TMT) is increasingly offered in Europe as an alternative to preservative treated timber. TMT durability in field tests as well as its moisture sorption behaviour in façade application was determined so as to consider its suitability for outdoor use. Additionally, abrasion and crack-formation of TMT deckings were examined and the optical appearance of a TMT façade was evaluated after 5 years of service. After 7.5 years exposure in ground contact, the various TMT materials tested were classed as “slightly durable” to “not durable” whereas the classification in above ground exposure as “very durable” to “moderately durable”, which was in line with the reduced moisture sorption of TMT in weathered application. Moreover, the TMT-decking showed less abrasion and crack-formation compared to references, though the TMT façade revealed considerable discoloration by weathering. Hence, the suitability of TMT for above ground use is suggested, but a surface treatment is obligatory if discoloration is objectionable.